A Proposed Long Wavelength Infra-red Metamaterial Absorber for THz Detection - Nilotpal; Singh A.K.; Upadhyay M.; Lata R.; Bhattacharyya S.; Chakrabarti P. (My University, 2025)
A long wavelength infrared metamaterial absorber using electric field driven LC (ELC) resonating structure is reported in this paper. The structure shows an absorption peak of 96.2% at 30 THz (10.00 μm), The structure is studied for oblique incidences under TE and TM polarizations. The structure behaves as an absorber for both TE and TM polarizations so long as the angle of incidence is within 60°. All the results are obtained using Ansys HFSS, based on Finite Element Method (FEM). The absorption characteristics is simultaneously verified using COMSOL-Multiphysics simulation software and they are found to be in good agreement. The proposed ultra-thin (λ/30) metamaterial absorber structure is expected to find potential application in THz spectroscopy, imaging techniques and sensing. © 2018 IEEE.